Climate change and extremes : implications on city livability and associated health risks across the globe - Walter Leal Filho and Liza Tuladhar and Chunlan Li and Abdul Lateef Babatunde Balogun and Marina Kovaleva and Ismaila Rimi Abubakar and Hossein Azadi and Felix Kwabena Donkor (International journal of climate change strategies and management, 2022)
Purpose: As global warming intensifies, climatic conditions are changing dramatically, potentially affecting specific businesses and cities’ livability. The temperature increase in cities significantly affects urban residents whose percentage is to reach about 70% by 2050. This paper aimed at highlighting the climate change risks in cities, particularly focusing on the threats to people’s health due to a continuous temperature increase. Design/methodology/approach: This study was conducted in three main steps. First, the literature review on the effects of climate change, particularly on the continuous temperature rise in cities, was conducted based on the publications retrieved from PubMed, Science Direct, Google Scholar and Research Gate. Second, the survey was conducted for the sample cities for one month. Third, the questionnaire was used to assess possible climate change threats to the livability of cities. Findings: The findings showed that urban areas are usually warmer than the surrounding rural areas, mainly due to the urban heat island effect, causing more hot days in metropolitan areas compared to rural areas. This paper outlines some mitigation and adaptation measures, which can be implemented to improve the livability in cities, their sustainability and the well-being of their populations. Originality/value: This study reports on the climate change impacts on the health and livability of 15 cities, in industrialized and developing countries. It examines the average and maximum temperature and relative humidity of each city and its correlation with their livability. It was complemented by a survey focused on 109 cities from Africa, Asia, Europe, Latin America, North America and Oceania.
Keywords: Extreme weather events; Food security; Health condition; Increasing temperatures; Literature review; Rural areas